2017
DOI: 10.1371/journal.pone.0185766
|View full text |Cite
|
Sign up to set email alerts
|

Treatment satisfaction with injectable disease-modifying therapies in patients with relapsing-remitting multiple sclerosis (the STICK study)

Abstract: BackgroundTreatment satisfaction in patients with relapsing-remitting multiple sclerosis (RRMS) may impact adherence and thus clinical outcomes. The objective of this study was to measure the satisfaction of patients with RRMS with injectable disease-modifying therapies (DMTs) and to evaluate the factors associated with treatment satisfaction.Material and methodsIn this observational retrospective study conducted in the neurology departments of 35 hospitals throughout Spain, demographic data, disease character… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 26 publications
(34 reference statements)
2
16
0
Order By: Relevance
“…Satisfaction with injectable administration was also significantly higher in adherent patients, supporting the levels of adherence observed. It is known that the main reasons for lack of satisfaction are treatment inconvenience (needing regular injections can affect acceptance of treatment), injection burden of IV, injectable DMTs, and injection site reactions 33,34. In this context, our patients who received medication with IV administration showed a statistically higher concern for these possible mild side effects; this was primarily true for young people and women, who also showed higher levels of compliance.…”
Section: Discussionmentioning
confidence: 77%
“…Satisfaction with injectable administration was also significantly higher in adherent patients, supporting the levels of adherence observed. It is known that the main reasons for lack of satisfaction are treatment inconvenience (needing regular injections can affect acceptance of treatment), injection burden of IV, injectable DMTs, and injection site reactions 33,34. In this context, our patients who received medication with IV administration showed a statistically higher concern for these possible mild side effects; this was primarily true for young people and women, who also showed higher levels of compliance.…”
Section: Discussionmentioning
confidence: 77%
“…Scores range from 0 (normal) to 8(bed-ridden) [15]. It is a valid patient-reported outcome of disability in MS [19]. Moreover, the study questionnaire included participants' socio-demographic data, including gender, age, level of education, region, and marital status of the participants.…”
Section: Methodsmentioning
confidence: 99%
“…In the past decade, several papers have reported on MS patient treatment satisfaction with DMT in various countries. [14][15][16][17][18][19][20] Since a patient's treatment experience is to a certain extent influenced by the local availability of particular drugs, country-specific data are needed. To the best of our knowledge, the study presented here is the first report dealing with treatment satisfaction in the Slovak MS population.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published study on treatment satisfaction with injectable DMT in Spain 19 reported an effectiveness score of 66.8, convenience 72.5 and global satisfaction 68.8. These scores for convenience and global satisfaction are slightly higher than in the SKARLET study (convenience 66.9, global satisfaction 63.8), but this is in line with our assumptions on country-specific differences.…”
Section: Discussionmentioning
confidence: 99%